Gender and age employment gaps within agrifood value chains in Bangladesh and Uganda - Ambler, Kate; Bloem, Jeffrey R.; Wagner, Julia (International Food Policy Research Institute, 2024)
Using data collected with a novel sampling approach for agrifood value chains in Bangladesh (rice and potato) and Uganda (arabica coffee and soybean), this study documented meaningful gender and age employment gaps within intermediary sections of the value chains, which include trading , processing, and wholesaling activities. While agrifood value chains have potential to generate new jobs and close gaps for both women’s and youth employment in low- and middle-income countries, the study identifies large gender gaps in both operators of intermediary firms and those employed by these firms, as well as an age gap, with few youth operating intermediary firms. The brief offers recommendations for addressing systemic barriers that contribute to gender and age gaps in this “hidden middle” of agrifood value chains.